Ceria nanoparticles meet hepatic ischemia-reperfusion injury: the perfect imperfection - Ni, Dalong (Adv Mater, 2019)
The mononuclear phagocyte system (MPS, e.g., liver and spleen) is often treated as a ‘blackbox’ by nano-researchers in translating nanomedicines. Often, most of the injected nanomaterials are sequestered by the MPS, preventing their delivery to the desired disease areas. Here, we exploit this imperfection by applying nano-antioxidants with preferential liver uptake to directly prevent hepatic ischemia-reperfusion injury (IRI), which is a reactive oxygen species (ROS)-related disease. Ceria nanoparticles (NPs) were selected as a representative nano-antioxidant and detailed mechanism of preventing IRI was investigated. We found that ceria NPs effectively alleviated the clinical symptoms of hepatic IRI by scavenging ROS, inhibiting activation of Kupffer cells and monocyte/macrophage cells. The released pro-inflammatory cytokines were then significantly reduced and the recruitment and infiltration of neutrophils were minimized, which suppressed subsequent inflammatory reaction involved in the liver. The protective effect of nano-antioxidants against hepatic IRI in living animals and the revealed mechanism herein suggests their future use for the treatment of hepatic IRI in the clinic.